Street food in Eastern Europe: a perspective from an urban environment in Moldova - Albuquerque, G (2020)
Street food is popular in Eastern Europe, but its diversity and nutritional value are unknown. This study aimed to characterise the street food environment in Chisinau, Moldova, including the vending sites and vendors, food availability and nutritional composition of foods and beverages. All street food vending sites (single point of sale) located in a 1-km buffer centred on the main public market were systematically selected (n439;n328 participants). Data on vending sites' characteristics (mobility, type of physical set-up and access to electricity), operating periods and food availability were collected. Samples of the most commonly available foods of unknown composition were collected (twenty-eight home-made and twenty-four industrial). Macronutrients, Na and K were quantified through chemical analysis. Fruits, beverages and food other than fruits were available in 2 center dot 5, 74 center dot 3 and 80 center dot 8 % of the vending sites, respectively. Among the latter, 66 center dot 4 % sold only industrial foods (e.g. pretzels, biscuits, wafers, chocolate and ice cream), 21 center dot 5 % only home-made (e.g. savoury and sweet pastries) and 12 center dot 1 % both. Home-made foods presented larger serving sizes and energy/serving (median kJ/serving: 1312 center dot 5v.670 center dot 3,P= 0 center dot 022); industrial foods were more energy-dense (median kJ/100 g: 1797 center dot 0v.1269 center dot 8,P= 0 center dot 002). High SFA,trans-fat and Na contents were found, reaching 10 center dot 9 g/serving, 1 center dot 4 g/serving and 773 center dot 7 mg/serving, respectively. Soft drinks and alcoholic beverages were available in 80 center dot 7 and 42 center dot 0 % of the vending sites selling beverages, respectively. Concluding, industrial snacks and home-made pastries high in Na and unhealthy fat were frequent in Chisinau. Prevention of diet-related diseases in Moldova may benefit from the improvement of the nutritional profile of street food.